OROS Methylphenidate in Adolescents with ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The efficacy and tolerability of osmotic-release oral system (OROS) methylphenidate in adolescents with attention deficit hyperactivity disorder (ADHD) were evaluated in a multisite controlled study at the Massachusetts General Hospital, Boston, and other centers in the United States.